2021
DOI: 10.1186/s12967-021-03165-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of metabolism to improve efficacy during CAR-T cell manufacturing

Abstract: Chimeric antigen receptor T cell (CAR-T cell) therapy is a relatively new, effective, and rapidly evolving therapeutic for adoptive immunotherapies. Although it has achieved remarkable effect in hematological malignancies, there are some problems that remain to be resolved. For example, there are high recurrence rates and poor efficacy in solid tumors. In this review, we first briefly describe the metabolic re-editing of T cells and the changes in metabolism during the preparation of CAR-T cells. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 114 publications
1
38
1
1
Order By: Relevance
“…Naïve T cells (T N ) and T SCM have the capacity to persist and proliferate long-term in cancer patients, leading to improved clinical outcome (45). Hence, enriching these cell types, especially CAR + T SCM cells, has become a central focus in the development of next-generation CAR-T therapy (28)(29)(30)(31). Our studies have demonstrated that almost all qCART™-generated CAR-T cell products contain >90% T N and T SCM (> 70% T SCM in most cases) in both CD4 CAR + and CD8 CAR + T cell populations, regardless of (1) CAR construct design, (2) GOI size, and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naïve T cells (T N ) and T SCM have the capacity to persist and proliferate long-term in cancer patients, leading to improved clinical outcome (45). Hence, enriching these cell types, especially CAR + T SCM cells, has become a central focus in the development of next-generation CAR-T therapy (28)(29)(30)(31). Our studies have demonstrated that almost all qCART™-generated CAR-T cell products contain >90% T N and T SCM (> 70% T SCM in most cases) in both CD4 CAR + and CD8 CAR + T cell populations, regardless of (1) CAR construct design, (2) GOI size, and…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy for strengthening CAR-T efficacy is to enrich specific T cell subsets that possess superior capability to persist and attack cancer. Ever since Gattinoni et al described a class of immunological memory cells known as memory stem T cell (T SCM ) (27), several studies have demonstrated that T SCM is critical in facilitating successful adoptive T cell therapy (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells deplete glucose in the TME, inhibiting the anticancer immunity of T cells, NK cells, macrophages, and DCs that use glucose for anti-cancer activity ( Renner et al, 2017 ; Xia et al, 2021 ). Mechanistically, glycolysis is necessary to regulate IFNγ production by T cells, and the restricted use of glucose in the TME limits Ca 2+ signaling, glycolysis, and cytokine production of TILs ( Rangel Rivera et al, 2021 ; Zhang et al, 2021 ). In fact, resistance to T cell therapy appears in cancer patients with overexpressed glycolysis enzymes.…”
Section: Cancer Metabolism and Immune Evasionmentioning
confidence: 99%
“…This result strongly supports the idea that elevated mitochondrial FAO leads to increased antigen presentation and IFN signaling to facilitate T cell-mediated cancer cell death. Moreover, increased mitochondrial metabolism and FAO in T cells, improves T cell survival and functionality, enhancing sensitivity to anti-PD-1 therapy (Chowdhury et al, 2018;Zhang et al, 2021) in other cancer types. Interestingly, a similar induction of IFN signaling has been revealed using RNA-seq analysis in human melanoma cells and mouse B16 melanoma treated with specific inhibitors of the FA desaturase SCD1.…”
Section: Melanoma Metabolism a Tool To Boost Immunotherapymentioning
confidence: 99%